2003
DOI: 10.1002/ajmg.a.20082
|View full text |Cite
|
Sign up to set email alerts
|

Gorlin syndrome with ulcerative colitis in a Japanese girl

Abstract: We present the case of a 14-year-old Japanese girl who had both Gorlin syndrome and ulcerative colitis. She had complained of blood stools for 6 months and severe scoliosis from her infancy. Physical examination revealed multiple nevi, palmar and plantar pits, jaw cysts, and calcification of the falx cerebri, leading to the diagnosis of Gorlin syndrome. Total colonoscopy revealed an edematous and spotty bleeding mucosa extending from the anus to the transverse colon. Histological examination was also compatibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Exon 1 was not included in the study due to its diversity at the 5ʹ‐extreme end. Only exon 1b is able to inhibit SMO activity fully, but this exon has not yet been investigated due to its extremely GC‐rich sequence …”
Section: Discussionsupporting
confidence: 90%
“…Exon 1 was not included in the study due to its diversity at the 5ʹ‐extreme end. Only exon 1b is able to inhibit SMO activity fully, but this exon has not yet been investigated due to its extremely GC‐rich sequence …”
Section: Discussionsupporting
confidence: 90%
“…Among 14 patients with NBCCS, PTCH mutations were found in 11. Some of the mutations have already been reported (Fujii et al 1999, Fujii et al 2003a, Fujii et al 2003b) and some will be reported elsewhere.…”
Section: Methodsmentioning
confidence: 86%
“…The most common type of PTCH1 mutation is an insertion or deletion that causes a frameshift and leads to premature termination of the PTCH1 translation. We have identified diverse PTCH1 mutations in Japanese Gorlin syndrome patients . Despite exhaustive analysis, PTCH1 mutation was not able to be identified in some patients.…”
Section: Genetic Testingmentioning
confidence: 96%